CHF5074 restores visual memory ability and pre‐synaptic cortical acetylcholine release in pre‐plaque Tg2576 mice. (28th January 2013) - Giuliani, Alessandro; Beggiato, Sarah; Baldassarro, Vito A.; Mangano, Chiara; Giardino, Luciana; Imbimbo, Bruno P.; Antonelli, Tiziana; Calzà, Laura; Ferraro, Luca
Abstract CHF5074, a new microglial modulator, attenuates memory deficit in Alzheimer's disease transgenic mice. In this study, the effect of an acute or subacute CHF5074 treatment on in vivo novel object recognition test and on [3H]Acetylcholine (ACh) and GABA release in pre‐plaque (7‐month‐old) Tg2576 mice have been compared with those induced by the γ‐secretase inhibitor LY450139 (semagacestat). Vehicle‐treated Tg2576 mice displayed an impairment of recognition memory compared with wild‐type animals. This impairment was recovered in transgenic animals acutely treated with CHF5074 (30 mg/kg), while LY450139 (1, 3, 10 mg/kg) was ineffective. In frontal cortex synaptosomes from vehicle‐treated Tg2576 mice, K+‐evoked [3H]ACh release was lower than that measured in wild‐type mice. This reduction was absent in transgenic animals subacutely treated with CHF5074 (30 mg/kg daily for 8 days), while it was slightly, not significantly, amplified by LY450139 (3 mg/kg daily for 8 days). There were no differences between the groups on spontaneous [3H]ACh release as well as spontaneous and K+‐evoked GABA release. These results suggest that CHF5074 has beneficial effects on visual memory and cortical cholinergic dysfunctions in pre‐plaque Tg2576 mice. Together with previous findings, these data suggest that CHF5074 could be a possible candidate for early Alzheimer's disease therapeutic regimens.